EFFECTS OF INTENSITY AND DURATION OF EXERCISE ON TOTAL LEUKOCYTE COUNT IN NORMAL SUBJECTS - Ali, Shaukat; Ullah, Farman; Ullah, Habib (Journal of Ayub Medical College Abbottabad, 2002)
Background: Leucocytes the mobile units of the protective system of the body, may circulate freely in the blood, adhere to the vascular endothelium in sites where blood flow is relatively slow and then once again re-enter the circulation in a process of continuous exchange. This process of continuous exchange of leucocytes is influenced by proper stimulation such as exercise. This study was done to observe the effects of intensity and duration of exercise on total leucocyte count. Methods: Two groups of normal healthy male adult subjects were exercised on treadmill. Group-I performed exercise by running for a duration of 2-3 minutes, at 7% grade (4 degree inclination) and at constant speed ranging from 7.5 to 9 Km/hour while group-II walked on treadmill for a duration of 7-10 minutes at zero grade and at constant speed ranging from 5 to 6 Km/hour. Blood sample was drawn before exercise, immediately after exercise and after 30 minutes of rest after the exercise. Total leukocyte count was then done by improved Neubauer haemocytometer. Results: The mean of pre-exercise total leucocyte count of Group-I subjects (n=15) was 9750 ± 384.47/µl, while immediately after exercise the mean total leucocyte count increased to 17856.66 ± 1213.24/µl and after 30 minutes rest, it came down to 10396.67 ± 648.35/µl. Whereas, the mean of total leucocyte count of group-II subjects (n=15) was 10266.66 ± 307.60/µl pre-exercise, 16336.66 ± 866.30/µl immediately post-exercise and 1162.33 ± 718.85/µl at 30 minutes post-exercise. The total leucocyte count increased significantly immediately after exercise and it significantly decreased after 30 minutes of rest but was still higher than the pre-exercise count in both the groups Conclusion: It is clearly reflected by this study that the magnitude of exercise-induced leucocytosis is higher in exercise of more intensity and less duration.